Self-care behavior in hemodyalized patients in Ibarra, Ecuador - Hidrobo Guzmán, José Fabián; Jaramillo Jácome, Karen; Morejón Jácome , Gladys; Cárdenas Robles , Edison Daniel (Enfermería Cuidándote, 2024)
Introduction: The increase of patients with chronic kidney disease (CKD) on haemodialysis treatment in Ecuador and the complexity of care, points to the validity and importance of applying Orem's Theory, being relevant in the context of CKD, since knowledge about self-care behaviours can help to avoid complications in these patients.Objective: To analyse the health self-care behaviours of haemodialysis patients at a dialysis centre in Ibarra, based on Orem's theory.Material and Methods: A quantitative, observational, cross-sectional study with a sample of 30 haemodialysis patients of both sexes who met the inclusion criteria; the questionnaire Assessment of self-care of patients on hemodialysis treatment with a 0.86 Crombach's alpha reliability was used for data collection, applied during the third quarter of the year 2021.Results: 50% of the group presented an inadequate level of self-care in health and 60% of the patients established self-care behaviours as substantially adequate. The diagnostic outcome variables of the self-care test and the self-care behavioural factor on rest and sleep habits were significantly associated. There is a positive correlation between the self-care test diagnosis in haemodialysis patients and self-care behaviours.Conclusion: The group of patients evaluated show a deficit in self-care practices, and self-care behaviours are also a factor involved in the test diagnosis score.
Keywords: Chronic Kidney Disease; Hemodialysis; Orem Self-Care; Self-Care